The impact of telephonic wellness coaching on weight loss: A "Natural Experiments for Translation in Diabetes (NEXT‐D)" study. Issue 2 (26th January 2017) - Schmittdiel, Julie A.; Adams, Sara R.; Goler, Nancy; Sanna, Rashel S.; Boccio, Mindy; Bellamy, David J.; Brown, Susan D.; Neugebauer, Romain S.; Ferrara, Assiamira
Abstract : Objective: To evaluate the impact of a population‐based telephonic wellness coaching program on weight loss. Methods: Individual‐level segmented regression analysis of interrupted time series data comparing the BMI trajectories in the 12 months before versus the 12 months after initiating coaching among a cohort of Kaiser Permanente Northern California members ( n = 954) participating in The Permanente Medical Group Wellness Coaching program in 2011. The control group was a 20:1 propensity‐score matched control group ( n = 19, 080) matched with coaching participants based on baseline demographic and clinical characteristics. Results: Wellness coaching participants had a significant upward trend in BMI in the 12 months before their first wellness coaching session and a significant downward trend in BMI in the 12 months after their first session equivalent to a clinically significant reduction of greater than one unit of baseline BMI ( P < 0.01 for both). The control group did not have statistically significant decreases in BMI during the post‐period. Conclusions: Wellness coaching has a positive impact on BMI reduction that is both statistically and clinically significant. Future research and quality improvement efforts should focus on disseminating wellness coaching for weight loss in patients with diabetes and those at risk for developing the disease.